2023
DOI: 10.1007/s00210-023-02436-2
|View full text |Cite
|
Sign up to set email alerts
|

[8] and [10]-Gingerol reduces urothelial damage in ifosfamide-induced hemorrhagic cystitis via JAK/STAT/FOXO signaling pathway via IL-10

Abstract: Acrolein is the main toxic metabolite of Ifosfamide (IFO) that causes urothelial damage by oxidative stress and in ammation. Here we investigate the molecular mechanism of action of gingerols, Zingiber o cinale bioactive molecules, as an alternative treatment for ifosfamide-induced hemorrhagic cystitis. Female Swiss mice were randomly divided into 5 groups: control; IFO; IFO + Mesna; and IFO + [8]-or [10]gingerol. Mesna (80 mg/kg, i.p.) was given 5 minutes before, 4 and 8 hours after IFO (400mg/kg, i.p.).Ginge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…5A). Among the 10 activated pathways, previous studies have shown that JAK2/STAT3 could activate the FOXO signaling pathway (43–45), and JAK2/STAT3 could be activated via RAGE (46). In addition, the FOXO signaling pathway has been proved to induce muscle atrophy in previous studies (47,48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5A). Among the 10 activated pathways, previous studies have shown that JAK2/STAT3 could activate the FOXO signaling pathway (43–45), and JAK2/STAT3 could be activated via RAGE (46). In addition, the FOXO signaling pathway has been proved to induce muscle atrophy in previous studies (47,48).…”
Section: Resultsmentioning
confidence: 99%
“…The above study identified the RAGE ligand, S100B, as a novel factor able to induce muscle atrophy via a p38 mitogen-activated protein kinase/myogenin axis and STAT3-dependent myoblast determination protein 1 degradation. Previous study has also shown that the activation of JAK2/STAT3 could induce muscle wasting (53), and previous studies also proved that JAK2/STAT3 was able to activate FOXO, thus leading to a series of subsequent biological processes, including muscle wasting (43), age-related disease (44), or reduction of urothelial damage in ifosfamide-induced hemorrhagic cystitis (45). Notably, as we have mentioned previously, RAGE is also one of important receptors for SAA (41,42).…”
Section: Discussionmentioning
confidence: 97%